A qualitative study about the experiences of ethnic minority pregnant women with gestational diabetes. Issue 3 (17th January 2019) - Dayyani, Ida; Terkildsen Maindal, Helle; Rowlands, Gillian; Lou, Stina
Abstract : Background: Gestational diabetes mellitus demands rapid health behaviour changes for the pregnant woman to obtain stable blood glucose levels. In Denmark, the general incidence of gestational diabetes mellitus is about 3%, but more than 4.5% among non‐Western immigrants and descendants. Women belonging to ethnic minorities may be particularly challenged by health behaviour changes due to educational, language and cultural barriers. Aim: To explore how non‐Western ethnic minority pregnant women in Denmark experience the hospital‐based information about gestational diabetes mellitus and how they integrate this information into their everyday life. A secondary aim was to investigate how health literacy and distributed health literacy affect this process. Methods: Semistructured, qualitative interviews with 11 women. Thematic analysis was conducted with a special focus on health literacy as analytical approach. Results: Three themes were identified: Reaction to the diagnosis, Everyday life and Information needs. All women felt sad and worried by the diagnosis. Some struggled to implement the recommended behaviour changes, and many lacked supports from their spouse. The hospital‐based information was positively evaluated, but in some cases, the information was misunderstood. Social networks, language skills, and the ability to seek and assess information were important factors influencing the degree to which the women experienced gestational diabetes mellitus to be a challenge. Conclusion: Women were generally satisfied with the hospital‐based information. Women with low health literacy/poor Danish language skills seem to be most challenged by the diagnosis. Future research should examine ways to organise patient‐centred health care while simultaneously supporting women's opportunity to increase health literacy through, for example social network and the Internet.